X-RAY SPECTROMETRY FROM A MICROCT SYSTEM - Hugo Romberg; Caio Márcio Sorrentino de Freitas Santos; Tâmara Porfírio Teixeira; Olga Maria Oliveira Araújo; Davi Ferreira Oliveira; Ricardo Tadeu Lopes (Brazilian Journal of Radiation Sciences, 2021)
X-ray production is of fundamental importance for several applications, among these is the Microcomputed tomography technique (microCT). It is used to conduct studies in different areas of research such as industry, dentistry, archaeology and biomedicine. In this study, X-ray spectra were acquired with different filtering configurations in order to better understand the energy behavior of a X-ray beam used in a microCT system. Unfiltered spectra were acquired for voltages of 20 up to 80 kV and filtered spectra for voltages from 40 up to 120 kV. As results, the mean energy values of each filtered and unfiltered beams from 40 to 120 kV were obtained. These values were calculated based on the spectra evaluation, as well as the value of attenuation that each filtering systems generated in the spectra of 60 and 70 kV. To compose the filtration systems metallic physical filters of aluminum and copper were used. Spectra acquisition was done using a semiconductor detector, model XR-100CdTe, manufactured by Amptek.